2005
DOI: 10.2174/138161205774580732
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction of Dietary Lipids Carried in Chylomicron Remnants with Cells of the Artery Wall: Implications for Atherosclerosis Development

Abstract: The development of atherosclerotic lesions in the artery wall is a complex process involving the endothelium, lipid engorged macrophages (foam cells) and smooth muscle cells. In recent years it has become clear that chylomicron remnants, the lipoproteins which carry lipids of dietary origin in the blood, are strongly atherogenic, and there is increasing evidence to indicate that this is due to direct interaction of the remnant particles with cells of the artery wall. Chylomicron remnants have been demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 109 publications
(175 reference statements)
2
50
0
2
Order By: Relevance
“…43 Cholesterol uptake studies have confirmed that these receptors are indeed functional and in the presence of various forms of cholesterol, SMCs can become "lipid laden." 32 In vitro, the LDL receptor on SMCs can mediate the uptake of unmodified LDL, 36 acetylated LDL, 44 enzymatically modified LDL, 35 as well as chylomicron remnants [45][46][47] in the same manner demonstrated in macrophages. The scavenger receptor CXCL16/SR-PSOX, which is found in atherosclerotic but not healthy vessels, is also associated with the uptake of oxidized LDL into human SMCs.…”
Section: Lipid Uptake By Smcsmentioning
confidence: 88%
“…43 Cholesterol uptake studies have confirmed that these receptors are indeed functional and in the presence of various forms of cholesterol, SMCs can become "lipid laden." 32 In vitro, the LDL receptor on SMCs can mediate the uptake of unmodified LDL, 36 acetylated LDL, 44 enzymatically modified LDL, 35 as well as chylomicron remnants [45][46][47] in the same manner demonstrated in macrophages. The scavenger receptor CXCL16/SR-PSOX, which is found in atherosclerotic but not healthy vessels, is also associated with the uptake of oxidized LDL into human SMCs.…”
Section: Lipid Uptake By Smcsmentioning
confidence: 88%
“…The inflammatory process is at the centre of the atherosclerotic lesion. Chylomicron remnants induce macrophage foam cell formation [93,94]. The fatty acid composition of chylomicron remnants markedly influences the formation of macrophage foam cells.…”
Section: Chylomicron and Atherosclerosismentioning
confidence: 99%
“…CMR have been shown to penetrate the artery wall and to be retained within the intima [28][29][30], and remnant-like lipoproteins have been found in human atherosclerotic plaque [31][32][33]. CMR and TRLs have also been demonstrated to cause endothelial dysfunction [34][35][36][37][38], macrophage foam cell formation [34,39] and the proliferation of VSMCs [34]. Other pro-inflammatory and potentially atherogenic effects of postprandial lipoproteins include activation of leukocytes, promoting adhesion to the endothelium and invasion of the artery wall [12,40].…”
Section: Postprandial Hyperlipidemia As a Risk Factor For Atherosclermentioning
confidence: 99%
“…Postprandial hyperlipidemia is a feature of common, often inter-related, metabolic diseases, including obesity, insulin resistance, the metabolic syndrome (a combination of obesity, hypertension, insulin resistance/diabetes), non alcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus [12,34,81] (Fig. 1).…”
Section: Postprandial Lipemia and Metabolic Dis-easesmentioning
confidence: 99%
See 1 more Smart Citation